Human Adipose‐Derived Stromal Cell Isolation Methods and Use in Osteogenic and Adipogenic In Vivo Applications. (13th February 2018) - Brett, Elizabeth; Tevlin, Ruth; McArdle, Adrian; Seo, Eun Young; Chan, Charles K.F.; Wan, Derrick C.; Longaker, Michael T.
Abstract: Adipose tissue represents an abundant and easily accessible source of multipotent cells, which may serve as excellent building blocks for tissue engineering. This article presents a newly described protocol for isolating adipose‐derived stromal cells (ASCs) from human lipoaspirate, compared to the standard protocol for harvesting ASCs established in 2001. Human ASC isolation is performed using two methods, and resultant cells are compared through cell yield, cell viability, cell proliferation and regenerative potential. The osteogenic and adipogenic potential of ASCs isolated using both protocols are assessed in vitro and gene expression analysis is performed. The focus of this series of protocols is the regenerative potential of both cell populations in vivo . As such, the two in vivo animal models described are fat graft retention (soft tissue reconstruction) and calvarial defect healing (bone regeneration). The techniques described comprise fat grafting with cell assisted lipotransfer, and calvarial defect creation healed with cell‐seeded scaffolds. © 2017 by John Wiley & Sons, Inc.